Multi‐resonator application on size reduction for retransmission‐based chipless RFID tag - A. K. M. Z. Hossain (Wiley, 2021)
Abstract Here, a ‘truncated C’‐shaped planar coupled line resonator for UWB retransmission‐based chipless RFID has been presented. The resonator is small compared to other existing resonators in the retransmission‐based chipless RFID family. Two different coded multi‐resonator prototype tags have been designed and validated with newly designed planar microstrip fingertip‐shaped antennas. A good agreement is found between simulation and measurement responses. From the system validation, different coding combinations have been extracted when all resonators are present (111111111) and when three resonators are absent (110110101). It is found that with this resonator, 9 bits can be imposed instead of the existing planar rectangular resonator that gives only 1 bit with a larger size. Hence, as much as 86.7% of the occupied area is reduced by the resonator presented in this work. This work is anticipated to motivate the researchers in developing UWB passive RFID tags with higher bit density and smaller sizes for item tagging and sensing applications.